Protest “Bitnish”: Political Communication Through Banners at Student Protests in Serbia (2024/2025) - Vladimira Ilić (Etnoantropološki Problemi)
This introductory paper focuses on protest banners, interpreted as a form of protest bitnish—a coined expression combining the notions of significance (bitan) and triviality (sitniš). In other words, banners are considered both as supplementary tools of grassroots political communication within significant political contexts and as indicators of how protest participants subjectively experience the political reality in Serbia. The empirical material was collected between December 2024 and March 2025 through field observation, note-taking, and photography, as well as via media sources. The research covers seven major protests involving students and citizens, held in Serbia’s university centers: Belgrade, Novi Sad, Kragujevac, Novi Pazar, and Niš. This study does not aim to provide a deep or groundbreaking content analysis of the banners from these protest events. Rather, drawing on general communication theory and, more specifically, political communication theory, it seeks to offer one possible classification of the extensive and dispersed empirical material, along with accompanying analytical commentary. The goal is to explore, at least partially, the potential of protest banners as a subject of scientific research—one that has so far been largely neglected—and to propose guidelines for future,thematically diverse and analytically more thorough studies of specific political communication and/or particular features of the student movement in question.